Of Journeys, Returns, and Transnational Subject Formations: Reflections on the Homeland/Hostland Dialectic in Donato Ndongo-Bidyogo's Novels - Boampong, Joanna (Research in African literatures, 2017)
A critical survey of the novelistic production of Donato Ndongo-Bidyogo reveals the existence of a dialectical relationship in the conceptualization of “home” and “abroad,” be it as a consequence of colonialism, exile, migration, or dictatorship. Studied together, the unnamed protagonist in the first two novels of his promised trilogy titled Hijos de la tribu [Sons of the Tribe], and Obama Ondo, the protagonist of his third novel, present intricate dimensions for examining questions relating to migration, exile, and the attendant issues of alienation, diasporic (re/de)constructions, and transcultural subject positioning, among others. With the aim of presenting perspectives from Hispanophone African literature, and broadening the scope of perspectives on debates surrounding the transnational/transmigrant subject, the diaspora, and the homeland/hostland dichotomy, this paper foregrounds the notion of “disruptions” (Salman Rushdie) germane to the movement and deterritorialization of transnational subjects through its reflections on the writings of three key texts in Hispanophone African literature.